Toward capacity-efficient, cost-efficient and power-efficient deployment strategy for indoor mobile broadband - Ashraf Awadelakrim Widaa; Jan Markendahl; Amirhossein Ghanbari (International Telecommunications Society (ITS), 2013)
Mobile operators nowadays tend to deploy dense heterogeneous layers of 3G and 4G networks in outdoor and indoor environments by adding more macrocells and smallcells (e.g. microcells, picocells and femtocells) in response to the increasing subscriber demand for coverage and capacity. The main driver and enabler behind this tendency is the phenomenon that around 80% of power consumption in mobile communication networks stems from the radio base stations. This situation makes mobile operators opt for the use low-power radio base stations to provide better coverage, capacity and a more environment-friendly operation. The use of low-power radio base stations leads to reduction of energy consumption in mobile communication networks power. The aim of this study is to conduct a comparative study between homogenous macrocell deployment and indoor smallcell deployments as alternative solutions for provision of the required indoor coverage and capacity. Moreover, the study highlights the importance of backhaul solutions being critical components in the smallcell network deployment. Furthermore, the scope of the study is extended to cover the investigation of the value of the heterogeneous (i.e. hybrid marcocell-femtocell) deployment scenario as a cost and power-efficient solution versus the homogenous marcocell deployment scenario in view of the variations in the mobile network traffic during the day. The main findings indicate that the CapEx and OpEx of the backhaul solution represent the major part of the total deployment cost in the indoor smallcell deployment scenario (i.e. femtocell case) compared to those of the macrocell deployment scenario. Nonetheless, the perceived saving in the total cost of ownership (TCO) resulting from the use of indoor smallcell (i.e. femtocell) remains a satisfactory and convenient motivation considering the traffic variation across the day, traffic distribution between indoor and outdoor locations and the keenness to use the spectrum resources more efficiently.
Keywords: 330; Backhaul; Cost; Capacity; Femtocell; fiber optic; HSPA; LTE; Microwave; Macrocell; Power Consumption; Deployment Strategies